Endangered; When newspaper archives crumble, history dies - Klinken, Gerry van (UI Scholars Hub, 2019)
Historians accept the death of oral sources, but expect newspaper archives in state institutions to be available for ever. Yet the majority of Indonesian newspaper titles in the National Library are today endangered. These crumbling papers are often the only copy in the world. This article frst reviews the role these archives have played in pathbreaking historical work, both Indonesian and foreign. Provincial newspapers record the chatter of a new, literate middle class that emerged in the middle of the tumultuous twentieth century. Indonesian historiography is transformed by the many surprises scholars experience when reading their lives there. When those sources turn to dust, historical research dies. This will affect not just specialized historians, but social scientists in many felds. The article then maps quantitatively the extent to which these papers are endangered. It fnally urges the social science community as a whole to campaign to save them through comprehensive digitization.